Anteseden Intensi Menggunakan Whistleblowing System - Muhammad Sufyan Juliandi Indra Jaya; Lilik Handajani; Dwi Putra Buana Sakti (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This article aims to analyze the influence of planned behavior, reporting channels anonymously, and personal costs to West Lombok district government employees. This research is categorized as quantitative research, using research samples on probability sampling and using the approach of purposive sampling. Sources were chosen purposively based on predetermined criteria, namely 1 PPK (Commitment Making Official), 1 Treasurer, and 2 Employees/staff from each Regional Apparatus Organization (OPD). The research data was processed by statistical tests using multiple linear regression methods. This study shows that planned behavior, reporting channel anonymity, and personal cost affects the intention to use the whistleblowing system. This research complements the related previous research literature on whistleblowing systems in government as well as provides new literature on impact planned behavior, reporting channel anonymity, and personal cost. This research has implications for reporting channels anonymously available can convince employees of protection and need to be disseminated to all employees so that they can be used effectively. In addition, if employees have the opportunity to avoid personal costs As a result of retaliation, employees within the organization will use a whistleblowing system that can protect their identity.